1976
DOI: 10.1139/o76-105
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative effects of unsaturated fatty acids in microbial mutants. VI. Selective growth responses of yeast and bacteria to cis-octadecenoate isomers

Abstract: The full series of positional isomers of cis-octadecenoate were tested for their suitability in meeting the nutritional requirement for unsaturated fatty acids by mutants of Escherichia coli and Saccharomyces cerevisiae that were unable to synthesize unsaturated fatty acids. Quantitative comparisons of the efficiencies of the various isomers showed a range from 0-48 cells per femtomole for the prokaryotic cells and 0-5 for eukaryotic cells. The delta 5 isomer was much more effective than the delta 6 isomer wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
0

Year Published

1978
1978
1991
1991

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 4 publications
4
7
0
Order By: Relevance
“…The 2t-t04t-and 13t-to 15t-18:1 isomers did not support growth, but 20:4 and 20:5 were twice as effective as 9c-18: 1; 9c, 12c-18:2; or 9c,12c,15c-IS:3 (216). In contrast to the t-l S: l isomers, the 7c-to IOc-I8: 1 positional isomers were all about equally effective in supporting growth of E. coli and S. cerevisiae cells (152). The 14c-to 17c-IS:1 acids did not support E. coli growth, and the 12c-to 17 c-IS: 1 acids did not support yeast cell growth.…”
Section: Growth Organ Size and Longevitymentioning
confidence: 79%
“…The 2t-t04t-and 13t-to 15t-18:1 isomers did not support growth, but 20:4 and 20:5 were twice as effective as 9c-18: 1; 9c, 12c-18:2; or 9c,12c,15c-IS:3 (216). In contrast to the t-l S: l isomers, the 7c-to IOc-I8: 1 positional isomers were all about equally effective in supporting growth of E. coli and S. cerevisiae cells (152). The 14c-to 17c-IS:1 acids did not support E. coli growth, and the 12c-to 17 c-IS: 1 acids did not support yeast cell growth.…”
Section: Growth Organ Size and Longevitymentioning
confidence: 79%
“…In these models, the cells made no un saturated fatty acids, and the only acids capable of meeting the structural need of the cell membranes were from external sources. The prokaryote models provided an excellent system to quantitate the degree to which an exogenous unsaturated acid contributes to membrane fluidity (63,64), and growth in the presence and absence of cAMP indicated differences among these acids in meeting the dynamic requirements for membrane assembly (90,109). In quantitating the need for an exogenous fatty acid, the models are relevant to the formation of mammalian membranes for which n-3 and n-6 fatty acids are only available from external sources.…”
Section: Membrane Biogenesis and Membrane Integritymentioning
confidence: 99%
“…Arachidonic, eicosapentaenoic and docosahexaenoic acids had the highest efficiencies; it was concluded that there was a direct correlation between greater number of double bonds and increased growth. A third study using a different desaturase mutant examined a number of cis-octadecenoate isomers and found all isomers between Δ7 and Δ12 able to support extensive growth (82). The Δ6 isomer was also effective, which is in contrast to results from other studies (79,80) which showed no activity using this compound.…”
Section: Fatty Acids and Fungal Growthmentioning
confidence: 84%